Multitargeted tyrosine kinase inhibition produces discordant changes between 99mTc-MDP bone scans and other disease biomarkers: analysis of a phase II study of sunitinib for metastatic castration-resistant prostate cancer - Saylor, Philip J; Mahmood, Umar; Kunawudhi, Anchisa; Smith, Matthew R; Palmer, Edwin L; Michaelson, M Dror (The Journal of nuclear medicine (1978), 2012)
One of the central unanswered questions in prostate cancer research is the significance of tyrosine kinase inhibitor (TKI)-induced improvements in (99m)Tc-methylene diphosphonate ((99m)Tc-MDP) bone scans. Multitargeted tyrosine kinase inhibition has recently shown promise in the management of castration-resistant prostate cancer. In some cases, TKI inhibition has produced unprecedented improvements in bone metastases as detected by (99m)Tc-MDP bone scans. The significance of these improvements is not known. In order to gain insight about the effects of TKIs on bone scans in prostate cancer, we systematically evaluated images from a phase II study of sunitinib, a multitargeted TKI. We analyzed images and data from a previously reported open-label phase II study that enrolled 34 men with advanced castration-resistant prostate cancer. Participants received sunitinib in 6-wk cycles (50 mg daily; 4 wk on, 2 wk off). We examined baseline and 12-wk bone scan images. Partial response was defined as an improvement of at least 50% in previous metastatic lesions subjectively or a change from prior diffuse skeletal metastases (superscan) to recognizable individual metastatic lesions. Our primary objective was to define the incidence of at least partial bone scan response. We also examined concomitant changes in CT and prostate-specific antigen (PSA) evidence of disease. Analysis at 12 wk revealed 1 partial response by the response evaluation criteria in solid tumors (RECIST) and 2 confirmed PSA responses. There were 25 subjects who underwent bone scans at both time points (baseline and week 12) and who had bone metastases detectable at baseline. Within that group of 25, we found 5 bone scan partial responses and 1 complete response. None of those 6 subjects exhibited a PSA response (≥50% decline from baseline) or RECIST response. We found a relatively high rate of (99m)Tc-MDP bone scan response to sunitinib among men with metastatic prostate cancer. Further, we found that none of the subjects exhibiting bone scan responses experienced concordant improvements in PSA or CT evidence of disease by accepted criteria. This discordance argues that osteoblastic assessment provides an incomplete assessment of treatment-induced changes. Rational development of multitargeted TKIs for prostate cancer requires improved understanding of treatment-induced bone scan changes. Optimal imaging strategies may include evaluation of perfusion or direct tumor activity.